2022
DOI: 10.3389/fpsyg.2022.872544
|View full text |Cite
|
Sign up to set email alerts
|

Eco-anxiety in children: A scoping review of the mental health impacts of the awareness of climate change

Abstract: BackgroundYouth are increasingly aware of the negative effects of climate change on the planet and human health, but this knowledge can often come with significant affective responses, such as psychological distress, anger, or despair. Experiencing major “negative” emotions, like worry, guilt, and hopelessness in anticipation of climate change has been identified with the term eco-anxiety. Emerging literature focuses on adults' experience; however, little is known about the ways in which children and youth exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(56 citation statements)
references
References 82 publications
0
32
1
Order By: Relevance
“…5 Educators also need to proactively develop plans for addressing the effects of climate change on school operations, such as the ability to provide time outdoors or a need for temporary climate-related closures. 5…”
Section: Educatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Educators also need to proactively develop plans for addressing the effects of climate change on school operations, such as the ability to provide time outdoors or a need for temporary climate-related closures. 5…”
Section: Educatorsmentioning
confidence: 99%
“…Because many teens report feeling invalidated, providing safe spaces for adolescents to discuss their feelings without pathologizing their fears about climate change can be helpful . Adults could also model actions to care for the planet, provide hopeful but realistic messages about climate change, ensure adolescent representation on climate change efforts, and support adolescent-led advocacy …”
Section: Climate Change Efforts To Promote Hope Among Adolescentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial evidence of eco-anxiety in children is sparse. However, two recent scoping reviews indicated that youth and children experience emotional reactions in response to the awareness of climate change, which constitutes a form of eco-anxiety [ 30 , 31 ]. One of the most recent large-scale surveys of young people between the ages of 16 and 25 years across many different countries found that more than half (60%) of respondents were “very” or “extremely” worried about climate change, and 56% believed that “humanity is doomed” [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to the pandemic, the climate crisis is an existential threat to our world and especially youth have been found to be affected in their mental health and well-being because of climate change (Clemens et al, 2022;Sanson & Bellemo, 2021;Sciberras & Fernando, 2022). Besides the direct effect of climate change, i.e., natural disasters, on mental health and well-being, mental health is affected by indirect effects as well, including anxiety about the future, distress, and feelings of hopelessness and anger (Cianconi et al, 2020;Fritze et al, 2008;Léger-Goodes et al, 2022). It has been suggested that the rise in mental health problems and decreased well-being in children and adolescents (Collishaw, 2015;Pitchforth et al, 2019) is partly explained by the worry, fear, and anxiety youth experience about the impact of climate change on their future lives (Amnesty International, 2019;Bolton & Bhugra, 2020).…”
Section: Importance Of Well-being Research and Implicationsmentioning
confidence: 99%